2014
DOI: 10.3892/ijo.2014.2330
|View full text |Cite
|
Sign up to set email alerts
|

StarD13 is a tumor suppressor in breast cancer that regulates cell motility and invasion

Abstract: Breast cancer is one of the most commonly diagnosed cancers in women around the world. In general, the more aggressive the tumor, the more rapidly it grows and the more likely it metastasizes. Members of the Rho subfamily of small GTP-binding proteins (GTPases) play a central role in breast cancer cell motility and metastasis. The switch between active GTP-bound and inactive GDP-bound state is regulated by guanine nucleotide exchange factors (GEFs), GTPase-activating proteins (GAPs) and guanine-nucleotide diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 38 publications
19
52
1
Order By: Relevance
“…Also, these high risk patients showed reduced metastasis and recurrence free survival with no difference in overall survival when compared with to the low risk patient None of the groups showed any significant change as determined by Mann-Whitney U Test. 6 In contrast, another study showed that knockdown of DLC2 in the HepG2 hepatocellular carcinoma line showed increase cell motility in transwell migration assays. The graph is represented in scatter dot plot with mean 6 SEM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, these high risk patients showed reduced metastasis and recurrence free survival with no difference in overall survival when compared with to the low risk patient None of the groups showed any significant change as determined by Mann-Whitney U Test. 6 In contrast, another study showed that knockdown of DLC2 in the HepG2 hepatocellular carcinoma line showed increase cell motility in transwell migration assays. The graph is represented in scatter dot plot with mean 6 SEM.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another study showed that STARD13 was expressed at lower levels in stage I & II breast cancers compared to stage 0, however, its expression was elevated in higher grade tumors. 6 Knockdown of STARD13 resulted in less motility in 2D cultures, but increased invasiveness in 3D cultures. 6 The 3 0 UTR of STARD13 mRNA is targeted by the miR-125b microRNA and expression of a miR-125b mimic in the MCF7 cell line resulted in increased metastases in tumor xenografts.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations